Intraperitoneal gemcitabine chemotherapy is safe for patients with resected pancreatic cancer: final clinical and pharmacologic data from a phase II protocol and recommended future directions - Sugarbaker, Paul H. (J Gastrointest Oncol, 2021)
Worldwide, the surgical management of pancreas cancer using the Whipple procedure results in long-term survival in approximately 20% of patients when there is a R0 resection. Local recurrence within the resection site and peritoneal metastases are a prominent part of this treatment failure. Gemcitabine was used for a regional chemotherapy treatment strategy. Doses and schedules of chemotherapy routinely used for systemic treatment were administered as hyperthermic intraperitoneal chemotherapy (HIPEC) in the operating room. Then patients went on to receive 6 months of long-term normothermic intraperitoneal chemotherapy (NIPEC) with gemcitabine. Data was gathered to determine a pharmacologic rationale and safety of this monotherapy with gemcitabine. The use of intraperitoneal gemcitabine was well supported by pharmacologic data. The peritoneal surface exposure as measured by pharmacokinetic studies showed the area under the curve (AUC) of intraperitoneal concentration times time divided by plasma concentration times time to be 95–507. Regarding the safety of HIPEC gemcitabine in 12 patients, a single class III adverse event that resolved by radiologic intervention occurred. In patients with resected pancreas cancer treated with HIPEC gemcitabine the morbidity and mortality rate was not increased over historical data of resection alone. Also, six cycles of NIPEC gemcitabine were well tolerated in eight of eight eligible patients with seven patients completing 6 months of long-term intraperitoneal treatment. Local recurrence and peritoneal metastases were absent. Median survival was 29 months and five patients survived longer than 2 years. These early data suggest that intraperitoneal gemcitabine given under hyperthermic conditions in the operating theater and long-term through an intraperitoneal port is safe. Also, in this pilot study long-term local control with intraperitoneal gemcitabine occurred. Intraperitoneal gemcitabine may improve local-regional control of resected pancreas cancer. This may lead to more successful multimodality strategies.